Entering writers' rooms: reading interviews with novelists. Issue 3 (2nd September 2017) - Neave, Lucy
ABSTRACT: This paper examines the literary interview as a form, and as a source of research material for creative writing and literary studies. In the article, I discuss theoretical and methodological approaches to conversations with writers and the usefulness of the interview for creative writing scholars. Novelist Charlotte Wood published The Writer's Room: Conversations about Writing (2016) soon after her award-winning fifth novel, The Natural Way of Things (2015), appeared; the two books were constructed at around the same time. Through an interview I conducted with Wood about The Writer's Room and her reasons for speaking to contemporary writers, I assess the statements Wood makes in the introduction to her collection and explore the texture of literary interviews. The article examines what information interviews provide about an individual writer's working methods and looks at the emotions or affect around authors' writing lives as a means of gauging the utility of the interview for scholars and writers. I argue that while the apparent aim of the interview is to obtain insights into an author's praxis, related objectives may be to build connections between authors and their readers, and to augment communities of writers.